High-performance heavy rare earth-free sintered neodymium-iron-boron magnet and preparation method thereof
By controlling the distribution of Co elements in the grain boundary phase of the sintered NdFeB magnet, the (RE(Fe,M) phase is formed, which solves the problem of insufficient coercive force and temperature stability of the sintered NdFeB magnet, and the preparation of high-performance heavy-free rare earth magnets is realized, reducing the preparation cost.
Patent Information
- Application Number
- CN202411908490.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The coercive force of sintered NdFeB permanent magnet materials is low and the temperature stability is poor. The existing technology improves the performance of magnets by adding heavy rare earth elements, but due to the small reserves and high prices of heavy rare earth elements, the cost of magnet preparation increases.
By controlling the Co elements in the low melting point REzCo100-z alloy, they are mainly distributed in the grain boundary phase, and form (RE(Fe,M) phases with RE and Fe during high-temperature heat treatment, which consumes the Fe content in the thin grain boundary phase between adjacent Nd2Fe14B grains, reduces the magnetism of the grain boundary, enhances the demagnetization coupling effect, and significantly improves the coercive force of the magnet.
It realizes the high performance of heavy-free rare earth sintered NdFeB magnets, especially the characteristics of high coercive force, while reducing the preparation cost of magnets and improving production efficiency.
Smart Images

Figure CN119694770A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of permanent magnetic materials, in particular to a high-performance heavy rare earth-free sintered NdFeB magnet and a preparation method thereof. Background Art
[0002] Sintered NdFeB permanent magnet material is the permanent magnet functional material with the highest comprehensive magnetic properties and the widest application. In recent years, with the rise of new energy vehicles, intelligent manufacturing and other industries, sintered NdFeB magnets have become a key functional material to promote the rapid development of emerging industries, and also a key support for the development of related fields towards intelligence, miniaturization and lightweight. However, sintered NdFeB permanent magnet materials have low coercivity and poor temperature stability. Heavy rare earths are usually added to improve the coercivity and temperature resistance of the magnet. Due to the small reserves and high prices of heavy rare earth elements Dy and Tb, the preparation cost of NdFeB magnets has increased sharply, and the magnets are expensive. Therefore, the preparation of high-performance heavy rare earth-free sintered NdFeB magnets has become the direction of industrial development.
[0003] As an important alloying element, Co plays an important role in improving the Curie temperature and temperature stability of permanent magnets. However, the traditional method of adding Co is often to add it directly during the smelting stage (such as patent CN118039336A, patent CN108389711A), which makes the Co element mainly exist in RE2Fe 14 B phase, but when Co enters the main phase, it will reduce the remanence of the magnet and is not conducive to the improvement of coercivity. In addition, the patent application with publication number CN118020118A provides a sintered NdFeB magnet with high corrosion resistance and high magnetic properties and a preparation method thereof. Its main approach is to adjust the element Co to concentrate in the grain boundary phase, form a Nd3Co phase with the Nd-rich phase, and increase the electrode potential of the grain boundary phase to achieve the purpose of improving the corrosion resistance of the magnet. Subsequently, the patent continues to use the grain boundary diffusion process to improve the coercivity of the magnet. It can be seen that the role of introducing Co in this patent can only improve the corrosion resistance of the magnet, but cannot improve the magnetic properties. Summary of the invention
[0004] In view of this, the present invention provides a high-performance heavy rare earth-free sintered NdFeB magnet and a preparation method thereof to solve the problems raised in the above background technology. z Co 100-z Co in the alloy is mainly distributed in the grain boundary phase. During the high-temperature heat treatment, it forms (RE(Fe,M) phase with RE and Fe in the triangular grain boundary, consuming the adjacent Nd2Fe 14 The Fe content in the thin layer grain boundary phase between B grains reduces the magnetism of the grain boundary, enhances the demagnetization coupling effect, and significantly improves the coercivity of the magnet. The heavy rare earth-free sintered NdFeB magnet prepared by this method has high performance, especially high coercivity.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a high-performance heavy rare earth-free sintered NdFeB magnet, characterized by comprising the following steps:
[0007] S1. After the Co-free NdFeB alloy I and the Co-containing rare earth alloy II are smelted and crushed into fine powders respectively, the powders are mixed evenly to obtain a mixed powder; wherein the content of the Co element in the Co-containing rare earth alloy II is 20-40 wt.%; and the content of the Co element in the mixed powder is 2-10 wt.%;
[0008] S2. After the mixed powder is subjected to magnetic field pressing, static pressure treatment, vacuum sintering and heat treatment, a high-performance sintered NdFeB magnet is obtained.
[0009] As a further solution of the present invention: the composition of the Co-free NdFeB alloy I is RE x (Fe 1-a ,M a ) 100-x-y B y , wherein RE is a rare earth element excluding heavy rare earth Dy or Tb, 28wt.%≤x≤31wt.%; B is a boron element, 0.9wt.%≤y≤1.1wt.%; M is at least one of Ga, Ti, Cu, Al and Zr, a≤2wt.%; and Fe is the remainder of iron.
[0010] As a further solution of the present invention: the composition of the Co-containing rare earth alloy II is RE z Co 100-z , wherein RE is at least one of Pr and Nd, and z≥50wt.%.
[0011] As a further solution of the present invention: the smelting and crushing into fine powder are specifically as follows: first, the Co-free NdFeB alloy I and the Co-containing rare earth alloy II are rapidly solidified and smelted into alloy flakes I and alloy flakes II respectively; then, the alloy flakes I and alloy flakes II are crushed into powders I and powders II respectively by hydrogen crushing and air flow grinding process.
[0012] As a further solution of the present invention: the average particle size of the powder I is 2 μm to 5 μm; the average particle size of the powder II is 1 μm to 3 μm, and the average particle size of the powder I is greater than the average particle size of the powder II.
[0013] As a further solution of the present invention: the melting point of the Co-free NdFeB alloy I is 1000-1100°C; the melting point of the Co-containing alloy II is 500-800°C; the melting point of the Co-free NdFeB alloy I is higher than the melting point of the Co-containing rare earth alloy II.
[0014] As a further solution of the present invention: the static pressure treatment is specifically: cold isostatic pressing treatment at 150MPa to 250MPa, and the static pressing time is 30 to 60 seconds;
[0015] As a further solution of the present invention, the magnetic field pressing is specifically: placing the mixed powder in a magnetic field of not less than 2T to form a compact, the density of the compact being 3.6g / cm 3 ~4.0g / cm 3 ;
[0016] As a further solution of the present invention: the heat treatment includes two-stage heat treatment, namely primary heat treatment and secondary heat treatment; wherein: the temperature of the primary heat treatment is 800-950°C, and the time is 3h-6h; the temperature of the secondary heat treatment is 450-600°C, and the time is 3h-6h.
[0017] On the other hand, the present invention discloses a high-performance heavy rare earth-free sintered NdFeB magnet prepared by the above-mentioned preparation method, and the coercive force thereof is greater than 18 kOe.
[0018] As a further solution of the present invention: there are grain boundary rare earth-rich phases and triangular grain boundaries around the main phase grains, and RE (Fe, M) phases are generated in the triangular grain boundaries.
[0019] As a further solution of the present invention: the mass fraction of Co element in the main phase grains is q, the mass fraction in the grain boundary rare earth-rich phase is w, and the mass fraction of Co in the RE (Fe, M) phase is z, then w>q>z.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) By mixing Co-free NdFeB alloy I powder with Co-rich rare earth alloy II powder, the Co element is controlled in the grain boundary rare earth-rich phase of the final magnet, and RE (Fe, M) phase is generated in the triangular grain boundary phase, which consumes the Fe content in the thin layer of grain boundary phase, reduces the magnetism of the grain boundary, and enhances the demagnetization coupling effect; and the addition of low melting point auxiliary alloy II powder significantly increases the rare earth-rich phase of the magnet, enhances the fluidity and wettability of the grain boundary phase, and optimizes the grain boundary structure. The two work together to significantly improve the coercive force of the final magnet. The sintered NdFeB magnet obtained does not contain heavy rare earth elements and has the characteristics of high magnetic field stability.
[0022] (2) By adding the auxiliary alloy II powder rich in Co, the Co element inevitably diffuses into the main phase grains during the sintering process, so that a small amount of Co element exists in RE2Fe 14 In phase B, the Co element fully exerts its effect on RE2Fe without affecting the coercivity.14 The remanence temperature coefficient of phase B is improved. The sintered NdFeB magnet has the characteristics of low temperature coefficient.
[0023] (3) Neither the Co-free NdFeB alloy I powder nor the Co-rich auxiliary alloy II powder involves the addition of heavy rare earth elements, which can effectively reduce the preparation cost of the magnet and achieve the purpose of reducing costs and increasing efficiency; and the preparation process is simple, which can improve production efficiency and shorten the production cycle, is suitable for large-scale production, and has important guiding significance for the development of high-end application markets for enterprises. The sintered NdFeB magnets obtained have the characteristics of low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 (a) is the EPMA result of the sintered magnet obtained in Example 1, and (b) is the EPMA result of the sintered magnet in Comparative Example 1;
[0025] Figure 2 The line scan result of the sintered magnet obtained in Example 1 is shown; wherein the scan line line 1 starts from the main phase region of the magnet, passes through the light grey grain boundary phase, the white grain boundary phase, and finally reaches the main phase region;
[0026] Figure 3 This is a line scan result diagram of the sintered magnet obtained in Comparative Example 1; wherein the scan line line2 is located in the Co-free (cobalt-free) grain boundary phase region. DETAILED DESCRIPTION
[0027] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0029] Example 1
[0030] (1) The smelting components are Nd 30.5 Ti 0.2 Ga 0.1 Cu 0.2 Al 0.2 B 0.96 Fe bal The alloy powder I1 and the composition of Nd 80 Co 20alloy powder II1 (the subscripts corresponding to the above elements represent their mass fractions, the same below); using a rapid solidification smelting device to respectively prepare alloy strips I1 and alloy strips II1 from alloy powder I1 and alloy strips II1; using a hydrogen crushing and air flow milling process to respectively crush the strips I1 and alloy strips II1 into fine powders I1 with an average particle size of 3.5 μm and fine powders II1 with an average particle size of 1.2 μm; mixing the fine powders I1 and II1 uniformly at a mass ratio of 80:20 to obtain a mixed powder;
[0031] (2) The mixed powder was pressed into a mold in a 2.0 T magnetic field to obtain a density of 3.7 g / cm 3 The green compact is isostatically pressed at 200 MPa for 60 seconds, and then vacuum sintered and heat treated to obtain a high-stability sintered NdFeB magnet. The vacuum degree during sintering is better than 1×10 -2 Pa, the vacuum sintering temperature is 1030℃, and the sintering time is 6 hours; the heat treatment includes two processes: primary heat treatment and secondary heat treatment. The primary heat treatment temperature is 900℃, and the heat treatment time is 3 hours; the secondary heat treatment temperature is 600℃, and the heat treatment time is 3 hours.
[0032] In the above steps, high-purity argon or high-purity nitrogen is used to protect the materials to prevent them from contacting with oxygen or water vapor. Among them: the alloy smelting step, the hydrogen crushing step of crushing and powdering, the vacuum sintering and heat treatment steps of magnet preparation all use high-purity argon to protect the materials; the jet milling step of crushing and powdering, the powder mixing step, and the compression molding step of magnet preparation use high-purity nitrogen to protect the materials.
[0033] Comparative Example 1
[0034] The composition is Nd 30.5 Ti 0.2 Ga 0.1 Cu 0.2 Al 0.2 B 0.96 Fe bal Alloy I1 and Nd 80 Co 20 Alloy II1 is directly mixed at a mass ratio of 80:20 to obtain a composition of Nd 40.4 Ti 0.2 Co4Ga 0.1 Cu 0.2 Al 0.2 B 0.77 Fe bal Melting alloy powder III1
[0035] The alloy powder III1 is made into alloy ribbon III1 by using a rapid solidification smelting device; the ribbon III1 is crushed into fine powder vIII1 with an average particle size of 3.5 μm by using a hydrogen crushing and air flow grinding process; the fine powder III1 is molded in a 2.0 T magnetic field to obtain a density of 3.7 g / cm 3 The green compact was isostatically pressed at 200 MPa for 60 seconds, and then vacuum sintered and heat treated. The vacuum sintering and heat treatment process parameters and the protection requirements of the sample preparation process were the same as those in Example 1.
[0036] Example 2
[0037] (1) The smelting components are Nd 30.5 Ti 0.2 Ga 0.1 Cu 0.3 Al 0.2 B 0.97 Fe bal Alloy powder I2 and Nd 80 Co 20 alloy powder II2; using a rapid solidification smelting device to respectively prepare alloy strips I2 and alloy strips II2 from alloy powder I2 and alloy strips II2; using a hydrogen crushing and air flow milling process to respectively crush alloy strips I2 and alloy strips II2 into fine powder I2 with an average particle size of 2 μm and fine powder II2 with an average particle size of 1 μm; mixing fine powders I2 and II2 uniformly at a mass ratio of 90:10 to obtain a mixed powder;
[0038] (2) The mixed powder was molded in a 2.2T magnetic field and isostatically pressed at 220MPa for 60s to obtain a density of 4.0g / cm 3 The green compact is then vacuum sintered and heat treated to obtain a sintered NdFeB magnet. The vacuum degree during the sintering process is better than 8×10 -3 Pa, the vacuum sintering temperature is 1050℃, and the sintering time is 5 hours; the heat treatment includes two processes: primary heat treatment and secondary heat treatment. The primary heat treatment temperature is 850℃, and the heat treatment time is 3 hours; the secondary heat treatment temperature is 550℃, and the heat treatment time is 3 hours.
[0039] In the above steps, high-purity argon or high-purity nitrogen is used to protect the materials to prevent them from contacting with oxygen or water vapor. Among them: the alloy smelting step, the hydrogen crushing step of crushing and powdering, the vacuum sintering and heat treatment steps of magnet preparation all use high-purity argon to protect the materials; the jet milling step of crushing and powdering, the powder mixing step, and the compression molding step of magnet preparation use high-purity nitrogen to protect the materials.
[0040] Comparative Example 2
[0041] The composition is Nd30.5 Ti 0.2 Ga 0.1 Cu 0.3 Al 0.2 B 0.97 Fe bal Alloy powder I2 and Nd 80 Co 20的 Alloy powder II2 is directly mixed in a mass ratio of 90:10 to obtain a composition of Nd 35.5 Ti 0.18 Co2Ga 0.09 Cu 0.27 Al 0.18 B 0.87 Fe bal Melting alloy powder III2; using rapid solidification smelting equipment to make alloy strip III2 from alloy powder III2; using hydrogen crushing and air flow grinding to crush alloy strip III1 into fine powder III2 with an average particle size of 2 μm; pressing the fine powder III2 in a 2.2 T magnetic field, isostatic pressing for 60 s at 220 MPa to obtain a density of 4.0 g / cm 3 The green compact is then vacuum sintered and heat treated. The vacuum sintering and heat treatment process parameters and the protection requirements of the sample preparation process are the same as those in Example 2.
[0042] Example 3
[0043] (1) The smelting components are Nd 29.5 Ti 0.1 Ga 0.2 Cu 0.2 Al 0.2 B 0.98 Fe bal Alloy powder I3 and Nd 70 Co 30 alloy powder II3; using a rapid solidification smelting device to respectively prepare alloy strips I3 and alloy strips II3 from alloy powder I3 and alloy strips II3; using a hydrogen crushing and air flow grinding process to respectively crush alloy strips I3 and alloy strips II3 into fine powder I3 with an average particle size of 2.2 μm and fine powder II3 with an average particle size of 1.3 μm; mixing fine powders I3 and II3 uniformly at a mass ratio of 80:20 to obtain a mixed powder;
[0044] (2) The mixed powder was pressed into a 2T magnetic field to obtain a density of 3.6 g / cm 3 The green compact is isostatically pressed at 250 MPa for 30 seconds, and then vacuum sintered and heat treated to obtain a sintered NdFeB magnet. The vacuum degree during the sintering process is better than 6×10 -3Pa, the vacuum sintering temperature is 1070℃, and the sintering time is 4 hours; the heat treatment includes two processes: primary heat treatment and secondary heat treatment. The primary heat treatment temperature is 900℃, and the heat treatment time is 4 hours; the secondary heat treatment temperature is 600℃, and the heat treatment time is 3 hours.
[0045] In the above steps, high-purity argon or high-purity nitrogen is used to protect the materials to prevent them from contacting with oxygen or water vapor. Among them: the alloy smelting step, the hydrogen crushing step of crushing and powdering, the vacuum sintering and heat treatment steps of magnet preparation all use high-purity argon to protect the materials; the jet milling step of crushing and powdering, the powder mixing step, and the compression molding step of magnet preparation use high-purity nitrogen to protect the materials.
[0046] Comparative Example 3
[0047] The composition is Nd 29.5 Ti 0.1 Ga 0.2 Cu 0.2 Al 0.2 B 0.98 Fe bal Alloy powder I3 and Nd 70 Co 30 The alloy powder II3 is directly mixed in a mass ratio of 80:20 to obtain a composition of Nd 37.6 Ti 0.08 6G 0.16 Cu 0.16 Al 0.16 B 0.78 Fe bal Melting alloy powder III3; using a rapid solidification smelting device to make the smelted alloy powder III3 into an alloy strip III3; using a hydrogen crushing and air flow grinding process to crush the alloy strip III3 into fine powder III3 with an average particle size of 2 μm;
[0048] The fine powder III3 was pressed into a mold in a 2T magnetic field to obtain a density of 3.7 g / cm 3 The green compact is isostatically pressed at 250 MPa for 30 seconds, and then vacuum sintered and heat treated. The vacuum sintering and heat treatment process parameters and the protection requirements of the sample preparation process are the same as those in Example 3.
[0049] Example 4
[0050] (1) The smelting components are Nd 29.5 Ti 0.3 Ga 0.1 Cu 0.2 Al 0.2 B 0.97 Fe bal Alloy powder I4 and Nd60 Co 40 alloy powder II4; using a rapid solidification smelting device to respectively prepare alloy strips I4 and alloy strips II4 from alloy powder I4 and alloy strips I4; using a hydrogen crushing and air flow grinding process to respectively crush alloy strips I4 and alloy strips II4 into fine powder I4 with an average particle size of 5 μm and fine powder II4 with an average particle size of 3 μm; mixing fine powders I4 and II4 uniformly at a mass ratio of 80:20 to obtain a mixed powder;
[0051] (2) The mixed powder was pressed into a compact in a 2.1T magnetic field to obtain a density of 3.7 g / cm 3 The green compact is isostatically pressed at 200 MPa for 40 seconds, and then vacuum sintered and heat treated to obtain a sintered NdFeB magnet. The vacuum degree during the sintering process is better than 8×10 -3 Pa, the vacuum sintering temperature is 1080℃, and the sintering time is 4 hours; the heat treatment includes two processes: primary heat treatment and secondary heat treatment. The primary heat treatment temperature is 920℃, and the heat treatment time is 5 hours; the secondary heat treatment temperature is 520℃, and the heat treatment time is 5 hours.
[0052] In the above steps, high-purity argon or high-purity nitrogen is used to protect the materials to prevent them from contacting with oxygen or water vapor. Among them: the alloy smelting step, the hydrogen crushing step of crushing and powdering, the vacuum sintering and heat treatment steps of magnet preparation all use high-purity argon to protect the materials; the jet milling step of crushing and powdering, the powder mixing step, and the compression molding step of magnet preparation use high-purity nitrogen to protect the materials.
[0053] Comparative Example 4
[0054] The composition is Nd 29.5 Ti 0.3 Ga 0.1 Cu 0.2 Al 0.2 B 0.97 Fe bal Alloy powder I4 and Nd 60 Co 40 The alloy powder II4 is mixed uniformly in a mass ratio of 80:20 to obtain a composition of Nd 35.6 Ti 0.24 8g 0.08 Cu 0.16 Al 0.16 B 0.78 Fe balThe alloy III4 is smelted; the smelted alloy III4 is made into alloy strip III4 by using a rapid solidification smelting device; the alloy strip III4 is crushed into fine powder III4 with an average particle size of 5 μm by using a hydrogen crushing and air flow grinding process; the fine powder III4 is molded in a 2.1 T magnetic field to obtain a density of 3.7 g / cm 3 The green compact is isostatically pressed at 200 MPa for 40 seconds, and then vacuum sintered and heat treated. The vacuum sintering and heat treatment process parameters and the protection requirements of the sample preparation process are the same as those in Example 4.
[0055] Example 5
[0056] (1) The smelting components are Nd 28.5 Ti 0.2 Ga 0.1 Cu 0.2 Al 0.3 B 0.98 Fe bal Alloy powder I5 and composition Pr 80 Co 20 alloy powder II5; using a rapid solidification smelting device to respectively prepare alloy strips I5 and alloy strips II5 from alloy powder I5 and alloy strips I5; using a hydrogen crushing and air flow grinding process to respectively crush alloy strips I5 and alloy strips II5 into fine powder I5 with an average particle size of 4 μm and fine powder II5 with an average particle size of 2 μm; mixing fine powders I5 and II5 uniformly at a mass ratio of 80:20 to obtain a mixed powder;
[0057] (2) The mixed powder was pressed into a compact in a 2.2T magnetic field to obtain a density of 3.8 g / cm 3 The green compact is isostatically pressed at 220 MPa for 50 seconds, and then vacuum sintered and heat treated to obtain a sintered NdFeB magnet. The vacuum degree during the sintering process is better than 6×10 -3 Pa, the vacuum sintering temperature is 1100℃, and the sintering time is 3 hours; the heat treatment includes two processes: primary heat treatment and secondary heat treatment. The primary heat treatment temperature is 900℃, and the heat treatment time is 3 hours; the secondary heat treatment temperature is 480℃, and the heat treatment time is 4 hours.
[0058] In the above steps, high-purity argon or high-purity nitrogen is used to protect the materials to prevent them from contacting with oxygen or water vapor. Among them: the alloy smelting step, the hydrogen crushing step of crushing and powdering, the vacuum sintering and heat treatment steps of magnet preparation all use high-purity argon to protect the materials; the jet milling step of crushing and powdering, the powder mixing step, and the compression molding step of magnet preparation use high-purity nitrogen to protect the materials.
[0059] Comparative Example 5
[0060] The composition is Nd 28.5 Ti 0.2 Ga 0.1 Cu 0.2 Al 0.3 B 0.98 Fe bal Alloy powder I5 and composition Pr 80 Co 20 The alloy powder II5 is directly mixed in a mass ratio of 80:20 to obtain a composition of Pr 16 Nd 22.8 Ti 0.16 Co4Ga 0.08 Cu 0.16 Al 0.2 4B 0.78 Fe bal The alloy III5 is melted; the melted alloy III5 is made into alloy strip III5 by using a rapid solidification melting device; the alloy strip III5 is crushed into fine powder III5 with an average particle size of 4 μm by using a hydrogen crushing and air flow grinding process; the fine powder III5 is molded in a 2.2 T magnetic field to obtain a density of 3.8 g / cm 5 The green compact is isostatically pressed at 220 MPa for 50 seconds, and then vacuum sintered and heat treated. The vacuum sintering and heat treatment process parameters and the protection requirements of the sample preparation process are the same as those in Example 5.
[0061] Example 6
[0062] (1) The smelting components are Nd 29.5 Ti 0.3 Ga 0.2 Cu 0.2 Al 0.3 B 0.99 Fe bal Alloy powder I6 and Pr 80 Co 20 alloy powder II6; using a rapid solidification smelting device to respectively prepare alloy strips I6 and alloy strips II6 from alloy powder I6 and alloy strips II6; using a hydrogen crushing and air flow milling process to respectively crush alloy strips I6 and alloy strips II6 into fine powder I6 with an average particle size of 2.5 μm and fine powder II6 with an average particle size of 1.2 μm; mixing fine powders I6 and II6 at a mass ratio of 87.5:12.5 to obtain a mixed powder;
[0063] (2) The mixed powder was pressed into a compact in a 2.2T magnetic field to obtain a density of 3.9 g / cm 3 The green compact is isostatically pressed at 150 MPa for 50 seconds, and then vacuum sintered and heat treated to obtain a sintered NdFeB magnet. The vacuum degree during the sintering process is better than 8×10 -3Pa, the vacuum sintering temperature is 1090℃, and the sintering time is 3 hours; the heat treatment includes two processes: primary heat treatment and secondary heat treatment. The primary heat treatment temperature is 900℃, and the heat treatment time is 4 hours, and the secondary heat treatment temperature is 480℃, and the heat treatment time is 5 hours.
[0064] In the above steps, high-purity argon or high-purity nitrogen is used to protect the materials to prevent them from contacting with oxygen or water vapor. Among them: the alloy smelting step, the hydrogen crushing step of crushing and powdering, the vacuum sintering and heat treatment steps of magnet preparation all use high-purity argon to protect the materials; the jet milling step of crushing and powdering, the powder mixing step, and the compression molding step of magnet preparation use high-purity nitrogen to protect the materials.
[0065] Comparative Example 6
[0066] The composition is Nd 29.5 Ti 0.3 Ga 0.2 Cu 0.2 Al 0.3 B 0.99 Fe bal Alloy powder I6 and Pr 80 Co 20 The alloy powder II6 is directly mixed in a mass ratio of 87.5:12.5 to obtain a composition of Pr 10 Nd 25.8 Ti 0.26 Co 2.5 Ga 0.18 Cu 0.1 8Al 0.26 B 0.87 Fe bal Melting alloy III6; using a rapid solidification melting device to make alloy ribbon III6; using a hydrogen crushing and air flow grinding process to crush the alloy ribbon III6 into fine powder III6 with an average particle size of 2.5 μm; in a 2.2 T magnetic field, the fine powder III6 is molded to obtain a density of 3.9 g / cm 3 The green compact is isostatically pressed at 150 MPa for 50 seconds, and then vacuum sintered and heat treated. The vacuum sintering and heat treatment process parameters and the protection requirements of the sample preparation process are the same as those in Example 6.
[0067] Comparative Example 7
[0068] The component Pr4Nd 26.5 Tb 1.5 Ti 0.29 Co1Ga 0.19 Cu 0.19 Al 0.29 B 0.94 Fe balThe alloy III7 is melted by a rapid solidification melting device to form an alloy ribbon III7; the ribbon III7 is crushed into a powder III7 with an average particle size of 2.5 μm by a hydrogen crushing and air flow grinding process; the powder III6 is molded in a 2.2 T magnetic field to obtain a density of 3.9 g / cm 3 The green compact is isostatically pressed at 150 MPa for 50 seconds, and then vacuum sintered and heat treated. The vacuum sintering and heat treatment process parameters and the protection requirements of the sample preparation process are the same as those in Example 6.
[0069] Comparative Example 8
[0070] The component Pr4Nd 26.5 Ti 0.29 Co1Ga 0.19 Cu 0.19 Al 0.29 B 0.94 Fe bal The alloy III7 is melted by a rapid solidification melting device to form an alloy ribbon III7; the ribbon III7 is crushed into a powder III7 with an average particle size of 2.5 μm by a hydrogen crushing and air flow grinding process; the powder III6 is molded in a 2.2 T magnetic field to obtain a density of 3.9 g / cm 3 The green compact is isostatically pressed at 150 MPa for 50 seconds, and then vacuum sintered and heat treated. The vacuum sintering and heat treatment process parameters and the protection requirements of the sample preparation process are the same as those in Example 6.
[0071] Comparative Example 9
[0072] The component Pr4Nd 26.5 Ti 0.29 Co 15 Ga 0.19 Cu 0.19 Al 0.29 B 0.94 Fe bal The alloy III7 is melted by a rapid solidification melting device to form an alloy ribbon III7; the ribbon III7 is crushed into a powder III7 with an average particle size of 2.5 μm by a hydrogen crushing and air flow grinding process; the powder III6 is molded in a 2.2 T magnetic field to obtain a density of 3.9 g / cm 3 The green compact is isostatically pressed at 150 MPa for 50 seconds, and then vacuum sintered and heat treated. The vacuum sintering and heat treatment process parameters and the protection requirements of the sample preparation process are the same as those in Example 6.
[0073] The Co element distribution, coercive force, and remanence temperature coefficient of Examples 1 to 6 and Comparative Examples 1 to 9 were compared and tested, and the results are listed in Table 1; and the element distribution of the magnets in Example 1 and Comparative Example 1 was scanned using EPMA, as shown in FIG. Figure 1 As shown; Figure 2 The line scan results of the magnets in Example 1 and Comparative Example 1 are shown in Table 1. From the data comparison in Table 1, it can be found that the distribution of Co elements in the magnet can be controlled by using the technology of the present invention: the Co content in the grain boundary phase of the embodiment is significantly lower than that of the comparative example. Under the condition of the same composition, the coercive force of the embodiment is significantly higher than that of the comparative example. By comparing Example 6 with Comparative Example 7, it can be seen that the coercive force of the heavy rare earth-free magnet prepared by the present invention is equivalent to that of the magnet containing 1.5wt.% Tb in the formula.
[0074] Table 1 Relevant properties of the magnets obtained in Examples 1 to 6 and Comparative Examples 1 to 9
[0075]
[0076]
[0077] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0078] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.
Claims
1. A method for preparing a high-performance heavy rare earth-free sintered NdFeB magnet, characterized in that: The following steps are involved: S1. After the Co-free NdFeB alloy I and the Co-containing rare earth alloy II are smelted and crushed into fine powders respectively, the powders are mixed evenly to obtain a mixed powder; wherein the content of the Co element in the Co-containing rare earth alloy II is 20-40 wt.%; and the content of the Co element in the mixed powder is 2-10 wt.%; S2. After the mixed powder is subjected to magnetic field pressing, static pressure treatment, vacuum sintering and heat treatment, a high-performance sintered NdFeB magnet is obtained.
2. The preparation method according to claim 1, characterized in that: The composition of the Co-free NdFeB alloy I is RE x (Fe 1-a ,M a ) 100-x-y B y , wherein RE is a rare earth element excluding heavy rare earth Dy or Tb, 28wt.%≤x≤31wt.%; B is a boron element, 0.9wt.%≤y≤1.1wt.%; M is at least one of Ga, Ti, Cu, Al and Zr, a≤2wt.%; and Fe is the remainder of iron.
3. The preparation method according to claim 1, characterized in that: The composition of the Co-containing rare earth alloy II is RE z Co 100-z , wherein RE is at least one of Pr and Nd, and z≥50wt.%.
4. The preparation method according to claim 1, characterized in that: The smelting and crushing into fine powder are specifically as follows: firstly, the Co-free NdFeB alloy I and the Co-containing rare earth alloy II are rapidly smelted into alloy flakes I and alloy flakes II respectively; then, the alloy flakes I and alloy flakes II are crushed into powders I and II respectively by hydrogen crushing and air flow milling process.
5. The preparation method according to claim 4, characterized in that: The average particle size of the powder I is 2 μm to 5 μm; the average particle size of the powder II is 1 μm to 3 μm, and the average particle size of the powder I is greater than the average particle size of the powder II.
6. The preparation method according to claim 1, characterized in that: The Co-free NdFeB alloy I has a melting point of 1000-1100° C.; the Co-containing alloy II has a melting point of 500-800° C.; the melting point of the Co-free NdFeB alloy I is higher than the melting point of the Co-containing rare earth alloy II.
7. The preparation method according to claim 1, characterized in that: The static pressure treatment is specifically: cold isostatic pressing treatment at 150MPa to 250MPa, with a static pressing time of 30 to 60 seconds; and / or, The magnetic field pressing is specifically as follows: the mixed powder is placed in a magnetic field of not less than 2T and pressed into a compact, the density of the compact being 3.6g / cm 3 ~4.0g / cm 3 and / or, The heat treatment includes two stages of heat treatment, namely, primary heat treatment and secondary heat treatment; wherein: the temperature of the primary heat treatment is 800-950°C, and the time is 3h-6h; the temperature of the secondary heat treatment is 450-600°C, and the time is 3h-6h.
8. A high performance heavy rare earth-free sintered NdFeB magnet prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Its coercivity is greater than 18kOe.
9. The high performance heavy rare earth-free sintered NdFeB magnet according to claim 8, characterized in that: There are grain boundary rare earth-rich phases and triangular grain boundaries around the main phase grains, and RE (Fe, M) phases are generated in the triangular grain boundaries.
10. The high performance heavy rare earth-free sintered NdFeB magnet according to claim 9, characterized in that: The mass fraction of Co element in the main phase grains is q, the mass fraction in the rare earth-rich phase at the grain boundary is w, and the mass fraction of Co in the RE (Fe, M) phase is z, then w>q>z.
Citation Information
Patent Citations
Preparation method of sintered NdFeB magnet with high coercivity
CN108389711A
Sintered neodymium-iron-boron magnet with high corrosion resistance and high magnetic performance and preparation method of sintered neodymium-iron-boron magnet
CN118020118A
High-coercivity low-temperature coefficient neodymium-iron-boron magnet and preparation method and application thereof
CN118039336A